2017
DOI: 10.12988/ces.2017.710150
|View full text |Cite
|
Sign up to set email alerts
|

Approach to citation determinants of articles from Colombian engineering journals in Scopus

Abstract: The present text offers the results of an ordinary least squares (OLS) regression model that relates the number of citations of articles published in Colombian engineering journals in the Scopus database (Dyna; Engineering and Research; Engineering and University; and Faculty of Engineering Journal) to the following variables: journal, article, authors and affiliation. The model results show that the following variables are citation determinants: number of references, publication year, publication in Dyna and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…It was also found that: i) generally, the Colombian academic production on engineering comes mainly from Universidad Nacional and Universidad de Antioquia, and focuses on recognized Latin American journals such as DYNA, Revista Facultad de Ingeniería, and Revista Ingeniería e Investigación [2]; ii) it is characterized for the low citation of its articles [2], and iii) about half of the texts on Colombian engineering journals in Scopus are written in Spanish, by authors from non-English speaking countries [3].…”
Section: Introductionmentioning
confidence: 99%
“…It was also found that: i) generally, the Colombian academic production on engineering comes mainly from Universidad Nacional and Universidad de Antioquia, and focuses on recognized Latin American journals such as DYNA, Revista Facultad de Ingeniería, and Revista Ingeniería e Investigación [2]; ii) it is characterized for the low citation of its articles [2], and iii) about half of the texts on Colombian engineering journals in Scopus are written in Spanish, by authors from non-English speaking countries [3].…”
Section: Introductionmentioning
confidence: 99%